Problem of Language Representation in Native Speaker's Mind in Context of Language Border Zone: Studying Need in Karelian Language - - Viaut Alain; S A Moskvicheva (Peoples' Friendship University of Russia (RUDN University), 2013)
The article is focused on the issues related to the language representation in the native speaker's mind. It reveals that there are no direct dependencies between the structural language maturity, its historical development, and the speakers' need in its usage.